Eradication of tumors and development of anti-cancer immunity using STINGa targeted by pHLIP - Moshnikova, Anna; DuPont, Michael; Visca, Hannah; Engelman, Donald M.; Andreev, Oleg A.; Reshetnyak, Yana K. (Frontiers in Oncology, 2022)
Despite significant progress in the development of novel STING agonists (STINGa), applications appear to be challenged by the low efficiency and poor selectivity of these agents. A pH Low Insertion Peptide (pHLIP) extends the lifetime of a STINGa in the blood and targets it to acidic cancer-associated fibroblasts (CAFs), tumor-associated macrophages (TAMs), myeloid derived suppressor cells (mMDSCs) and dendritic cells (DCs). CAFs constitute 25% of all live cells within CT26 tumors, and M2-type TAMs and mMDSCs are the most abundant among the immune cells. The resulting activation of cytokines within the tumor microenvironment (TME) triggers the eradication of small (100 mm3) and large (400-700 mm3) CT26 tumors in mice after a single dose of pHLIP-STINGa. The tumor stroma was destroyed (the number of CAFs was reduced by 98%), intratumoral hemorrhage developed, and the level of acidity within the TME was reduced. Further, no tumors developed in 20 out of 25 tumor-free mice re-challenged by an additional injection of cancer cells. The therapeutic effect on CT26 tumors was insignificant in nude mice, lacking T-cells. Thus, targeted delivery of STINGa to tumor stroma and TAMs induces activation of signaling, potentially resulting in the recruitment and infiltration of T-cells, which gain access to the tumor core. The cytotoxic activity of T-cells is not impaired by an acidic environment and immune memory is developed.